Regional inequalities within the Visegrad group over the years 2000–2018 - Neszmélyi, György Iván; Vinogradov, Sergey; Nagy, Henrietta (European Spatial Research and Policy, 2023)
In the present study the authors examined the spatial disparities of the Visegrad four countries to see whether the lasting cooperation of the four countries resulted in harmonious economic development or increasing gaps between the years 2000 and 2018. Based on the research results it can be concluded that regional disparities between core and periphery regions of V4 countries still have not been eliminated to a significant extent. Despite the fact that the Visegrad Group has been in the EU for 18 years, the catching-up of its regions occurred with various speed, and no harmonised development can be observed within the Group.